2009
DOI: 10.1177/1756285608100416
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation and postpartum relapses in patients with multiple sclerosis

Abstract: Multiple sclerosis (MS) mainly affects young women during a life period with desire for children. Relapse rate decreases during pregnancy and rises after delivery. Therefore, studies on satisfactory postpartum relapse prevention and its efficacy are essential. Previous smaller and uncontrolled studies suggested that intravenous immunoglobulin (IVIG) administration reduced the relapse rate following delivery. The objective of our observational study was to compare the efficacy of IVIG application, treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 10 publications
1
38
0
6
Order By: Relevance
“…A postpartum therapy with intravenous immunoglobulin as well reduced the number of relapses [62,90]. Moreover, in contrast to IFN-β or GA, breastfeeding is possible while receiving IVIG.…”
Section: Reviewmentioning
confidence: 99%
“…A postpartum therapy with intravenous immunoglobulin as well reduced the number of relapses [62,90]. Moreover, in contrast to IFN-β or GA, breastfeeding is possible while receiving IVIG.…”
Section: Reviewmentioning
confidence: 99%
“…There have also been reports showing the efficacy of hIgG for relapse prevention and the attenuation of acute exacerbation . Finally, it is important to note that the safety of disease‐modifying therapies, such as IFN‐β, glatiramer acetate and fingolimod, has not been fully confirmed in pregnant or breastfeeding patients with RRMS . However, because of its safety, some investigators have gone ahead to recommended the use of hIgG therapy in this patient population .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with a potential therapeutic benefit of IVIg in patients with RR MS, a placebo-controlled trial in 91 patients with a first clinical episode suggestive of MS demonstrated a significantly lower risk of conversion to clinically definite MS on repeated IVIg treatment (26%) compared to placebo (50%, P = 0.03) treatment after 1 year [184]. Preliminary evidence indicates that IVIg treatment, which is safe during breast-feeding, might reduce the generally increased post-partum relapse frequency [185][186][187]. Randomised placebo-controlled trials in pregnant and breast-feeding females with MS should further explore this special but important indication.…”
Section: Reviewmentioning
confidence: 94%